Bacteria-based immunotherapy for cancer: a systematic review of preclinical studies - Zhou, Min; Tang, Yucheng; Xu, Wenjie; Hao, Xinyan; Li, Yongjiang; Huang, Si; Xiang, Daxiong; Wu, Junyong (Frontiers in Immunology, 2023)
Strategies for treating cancer are evolving quickly, especially immunotherapy has drawn a lot of attention. Emerging bacteria-based immunotherapies have shown promising results in numerous tumor models. However, the clinical application still exists blank. There is substantial evidence that naive bacteria, components, and derivatives modulate various immune pathways to exert immune effects. It is encouraged to create designer bacterial agents to enhance anti-tumor therapy. Now that the key mechanisms of bacterial impact on immune cells are well understood. The strongest clinical application chances currently are for the bacterial vaccine. Combining it with conventional therapies can successfully further boost anti-tumor effects. With an emphasis on clinical transformation concerns such as therapeutic modes, biosafety, and production methods, we outline the treatment modalities of advanced bacterial therapeutics. In conclusion, we are dedicated to offering a multifaceted viewpoint for optimizing clinical anti-tumor immunotherapy.